Weak Links in the Chain II : A Prescription for Health Policy in Poor Countries - Filmer, Deon; Hammer, Jeffrey S.; Pritchett, Lant H. (World Bank, Washington, DC, 2013)
This article presents an approach to public policy in health that comes directly from the literature on public economics. It identifies two characteristic market failures in health. The first is the existence of large externalities in the control of many infectious diseases that are mostly addressed by standard public health interventions. The second is the widespread breakdown of insurance markets that leave people exposed to catastrophic financial losses. Other essential considerations in setting priorities in health are the degree to which policies address poverty and inequality and the practicality of implementing policies given limited administrative capacities. Priorities based on these criteria tend to differ substantially from those commonly prescribed by the international community.